STUDY AND EVALUATION OF THE INTERNAL CONTROL SYSTEM DURING AN AUDIT CHECK - Abdieva Nargiza Shukhratovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The purpose of this article is to reveal the methods and significance of studying and evaluating the internal control system in auditing practice. To achieve this goal, the following tasks are set: to define the concepts of internal control and audit, to analyze the main components of the control system, to describe the goals and methods of its study and evaluation, as well as to consider the impact of internal control assessment on audit planning and conduct.